INNOVATIVE DEVELOPMENT TRENDS OF SMALL BUSINESS ENTREPRENEURSHIP IN THE DIGITAL ECONOMY CONDITION - TEPLIUK, MARIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the modern trends identification in the small businesses innovative development and their adaptability to the digital economy. The article presents the main characteristics of the digital economy and its impact on the small business’ innovative development. Transformation processes from idea generation, business idea formation to implementation of breakthrough innovations and small business enterprises activity are analyzed. The article considers, within the network intellectual digitization, technological trends: digital idea, smart applications and analytics, smart things, digital twins, cloud technologies, talk platforms, immersive experience, blockchain, managed models, prolonged adaptive risk and trust. Based on the results of strengths, weaknesses, opportunities and threats analysis, the most significant economic factors of industrial production development in Ukraine have been found out. The economic factors of the enterprises development under the conditions of Industry 4.0 are systematized. It shows the essence of the paradigm shifts in economy, that respond to the trend to globalization and setting up the information society, especially to the impact of the fourth industrial revolution. The authors have noted increased productivity and profitability of production and the rise of collaboration effectiveness between the economic entities. Such factors as the need to develop a new type of intellectual value chain, production of individual and customized goods with reasonable prices and use of learning factories have specific meaning in the framework of this problem. However, in the context of the Ukraine industrial policy within of Industry 4.0, certain systemic economic factors that could have a negative impact on the development of priority sectors of industry have been identified. The results obtained can be used by business entities implementing the decoded platform. At the same time, drivers of innovative development of modern business at the local and global level are identified, such as: staff and innovation culture, customer understanding, research and development, business processes and business model.